Linking Situational Analysis to Architecture and Urbanism. An Interdisciplinary Perspective - Kling, Norbert (Forum, qualitative social research, 2023)
Adele CLARKE, Carrie FRIESE and Rachel WASHBURN further expanded situational analysis (SA) with the publication of "Situational Analysis: Grounded Theory After the Interpretive Turn" (2018) and "Situational Analysis in Practice: Mapping Relationalities Across Disciplines" (2022). During the last two decades, SA has been applied to analyze a broad range of research problems across different disciplines. While the mutual relationship between social and material worlds is understood to be at the epistemic base of SA, so far only few studies have been focused on questions that are related to architectural and urban processes through which material worlds are produced, and even fewer on the professional work of designing such worlds and processes. This is paralleled by the lack of theorizing at the intersection of SA, architecture, and urbanism, which constitutes an impediment to interdisciplinary work. In this article, I argue that SA is relevant in architecture and urbanism, while proposing that architectural methods and modes of representation could also be useful for SA. I discuss a series of aspects that could help strengthen the links between SA, architecture, and urbanism, using research exemplars and student work produced in urban design to underpin the argument.